2018
DOI: 10.1128/aac.01198-18
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Biochemical Characterization of OXA-535, a Distantly Related OXA-48-Like β-Lactamase

Abstract: OXA-535 is a chromosome-encoded carbapenemase of JAB-1 that shares only 91.3% amino acid sequence identity with OXA-48. Catalytic efficiencies are similar to those of OXA-48 for most β-lactams, except for ertapenem, where a 2,000-fold-higher efficiency was observed with OXA-535. OXA-535 and OXA-436, a plasmid-encoded variant of OXA-535 differing by three amino acids, form a novel cluster of distantly related OXA-48-like carbapenemases. Comparison of and genetic environments suggests that an IS may be responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The in silico analysis showed that this assay should be able to detect all the IMP, NDM, VIM and KPC variants described as of December 2018. Among the OXA-48-like group, OXA-54 and OXA-535, described in the chromosome of Shewanella species [15,16] and OXA-436 identified on a plasmid in Enterobacter species, Citrobacter species and K. pneumoniae in Denmark [17] are unlikely to be detected.…”
Section: Discussionmentioning
confidence: 99%
“…The in silico analysis showed that this assay should be able to detect all the IMP, NDM, VIM and KPC variants described as of December 2018. Among the OXA-48-like group, OXA-54 and OXA-535, described in the chromosome of Shewanella species [15,16] and OXA-436 identified on a plasmid in Enterobacter species, Citrobacter species and K. pneumoniae in Denmark [17] are unlikely to be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Ω-loop (residues 143-165) and β5-β6-loop (residues 213-218) bordering the active site seem to be important determinants of OXA-48 activity, as discussed below. According to the β-lactamase database, at least 15 plasmid-encoded OXA-48 β-lactamases have been identified and validated (with further variants chromosomally encoded mainly in different Shewanella species 30,31 ). These variants differ from wild-type OXA-48 by certain amino acid substitutions or deletions.…”
Section: Introductionmentioning
confidence: 99%
“…All OXA-48 carbapenemase variants were correctly identified, including difficult-to-detect variants (OXA-244 and OXA-519), using biochemical tests such as Carba NP (12,13). It also detects very recently identified variants that have never been tested by ICA (OXA-484, -505, -517, and -793; Table 1) and the distantly related OXA-535 variant (14), which is the progenitor of OXA-436, a distantly related OXA-48 variant responsible for an outbreak associated with several enterobacterial species in Denmark (14-16). Moreover, OXA-163 and OXA-405, two OXA-48 variants that lack significant imipenemase activity (17) but with strong expanded-spectrum hydrolytic activity, were consistently detected.…”
mentioning
confidence: 96%